Huit initiatives bretonnes d’agriculture urbaine solidaire : quelles formes de justice et de démocratie alimentaire ? - Julien Noel; Catherine Darrot (VertigO, 2018)
This article presents the analysis of data from a regional inventory of territorial food solidarity initiatives in the Brittany region, conducted between 2013 and 2015. Based on a panorama of definitions of urban farming and (agri-)food justice/democracy, this material is explored with two directions. First, a sub-sample of 8 initiatives which are representative of the variety of urban situations observed is isolated and characterized. Those initiatives are then commented through four indicators defined for this study, in order to analyze the various ways of implementation of (agri-)food justice and democracy. Two indicators deal with the institutional role played by the public sector, two others deal with the degree of empowerment expected for the beneficiaries.